7 Answers

y^2 + 4y = 4
y^2 + 4y + 4 = 8
(y + 2)^2 = 8
y + 2 = +/ 2 sqrt(2)
y = 2 +/ 2 sqrt(2)

Assuming y2 is y^2 (ysquared), the equation isn’t: merely improve the words contained in the brackets and also you get: y^2 + 4y – y^2 = 6 Which simplifies to: 4y = 6 which isn’t a quadratic equation. yet when y2 isn’t ysquared yet truly 2y (i.e. 2 more effective with the help of y) then the equation is quadratic: y^2 + 2y = 6. desire this facilitates. suited answer? 😛

4 – 4y – y^2 = 0
y^2 – 4y + 4 = 0
(y^2 + 4y – 4) = 0
y^2 – 4y – 4 = 0
y = (b ± sqrt(b^2 – 4ac))/(2a)
y = ((4) ± sqrt((4)^2 – 4(1)(4)))/(2(1))
y = (4 ± sqrt(16 + 16))/2
y = (4 ± sqrt(32))/2
y = (4 ± sqrt(16 * 2))/2
y = (4 ± 4sqrt(2))/2
ANS : 2 + 2sqrt(2) or 2 – 2sqrt(2)

(y^2+4y4)=0 values are 4+4(2)^1/2/2 and 44(2)^1/2//
=2+2rt2 and 22rt2

factorize it by using the quadratic formula:
(b + sqrt(D))/2a, D is the determinant formula I gave you on the other question.
or using the completing the squares method
Source(s): do your own homework. 
corey, what part of your math assignment are you doing? (Just posting problems is not doing your assignment). I thought you knew that…

0.828 or4.828 (correct upto 3 digit)
Source(s): x=b+/sqrt(b^24ac)/21